Differences chronological age and dental age using Demirjian method based upon a study radiology using radiography panoramic at the Dental Hospital Hasanuddin University - Barunawaty Yunus; Yulia Wardhani (Journal of Dentomaxillofacial Science, 2016)
Background.Choronological age is assessed by the date, month, and year of birth. Several researches suggested that Chronological age may not be able to provide sufficient information regarding on human growth precisely. Chronological age, on the other hand, could not be used to assess  Maturity development rate of a patient, so it is necessary to assess the dental age. Dental age is age assessment method  by measuring human growth and development. Age estimation has important role in health field, Particularly  in dentistry as it will be beneficial in making appropriate diagnosis, Treatment plan, and prognosis. Tooth eruption estimation according to Demirjian Method conducted by assessing growth and development process of tooth using panoramic  radiography. Purpose. Determine the difference between Chronological Age and Dental Age Using Demirjian Method Based on Radiology Analysis of Panoramic Radiography. Method. This study was an observational analytic using Cross-sectional study, all data are observed once at the time. In this study,  the amount of sample reviewed were 30 samples, consisted of 4 – 9 years old children. Panoramic radiography were collected based on target population which fulfill Sample Criteria from reconciled patient of radiology department RSGM Unhas. The results were obtained by estimating the score of  dental age using Demirjian Method. After that, the Dental age and chronological age were analayzed to obtain the mean difference. Result. Based on wilcoxon test, mean value was obtain p:0.011 (p<0.05), this result shows that there is significant difference between chronological age and dental age. Conclusion.Chronological age and dental age can be assessed by reviewing the panoramic radiography using Demirjian Method